High-speed flat-detector computed tomography for temporal bone imaging and postoperative control of cochlear implants - Eisenhut, Felix; Manhart, Michael; Thimsen, Vivian; Mantsopoulos, Konstantinos; Iro, Heinrich; Hornung, Joachim; Dörfler, Arnd; Lang, Stefan; Taha, Lava (Neuroradiology, 2022)
Purpose: Flat-detector computed tomography (FD-CT) is the standard for cochlear implant (CI) imaging. FD-CT systems differ in technical characteristics. Our aim was an evaluation of two different FD-CT generations with different protocols and hardware regarding image quality, radiation dose, and scan time. Methods: Two temporal bone specimens (− / + CI = TB0/TB1) were scanned using three different scanners: two FD-CT systems with different scanning protocols (standard FD-CT: 20 s 70 kV, 20 s 109 kV; high-speed FD-CT [HS-FD-CT]: 7 s 109 kV, 9 s 109 kV, 14 s 72 kV) and MS-CT (5 s 120 kV). Acquired datasets were evaluated in consensus reading regarding qualitative and quantitative parameters: addressing CI- and cochlea-specific parameters, cochlea delineation, lamina spiralis ossea visibility, distinction of single CI electrodes, determination of intracochlear implant position, stapes delineation, and mastoidal septation were assessed. Addressing protocol-specific parameters, radiation dose (dose-length-product/DLP), and scan time were assessed. Results: Two HS-FD-CT protocols (14 s/9 s) provide higher or equivalent diagnostic information regarding CI- and cochlea-specific parameters compared to both standard FD-CT protocols. The fastest HS-FD-CT protocol (7 s)—providing inferior diagnostic information compared to all other FD-CT protocols—still exceeds MS-CT. The highest DLP was recorded for the 14 s HS-FD-CT protocol (TB1 = 956 mGycm); the lowest DLPs were recorded for the 7 s HS-FD-CT protocol (TB0 = 188 mGycm) and for MS-CT (TB0 = 138 mGycm), respectively. HS-FD-CT allows a significant reduction of scan time compared to standard FD-CT. Conclusion: High-speed FD-CT improves visualization of temporal bone anatomy and postoperative assessment of CIs by combining excellent image quality, fast scan time, and reasonable radiation exposure.
CRIS-Team Scopus Importer:2022-04-22
Keywords: Anatomy; Cochlear implant; Flat-detector computed tomography; Postoperative control; Temporal bone